Make : wearable electronics - Hartman, Kate, ....-; Jepson, Brian, 1967-; Dvorak, Emma, ....-; Demarest, Rebecca, ....- (Sebastopol : Maker Media, 2014)
Make: Wearable Electronics is intended for those with an interest in physical computing who are looking to create interfaces or systems that live on the body. Perfect for makers new to wearable tech, this book introduces you to the tools, materials, and techniques for creating interactive electronic circuits and embedding them in clothing and other things you can wear. Each chapter features experiments to get you comfortable with the technology and then invites you to build upon that knowledge with your own projects. Fully illustrated with step-by-step instructions and images of amazing creations made by artists and professional designers, this book offers a concrete understanding of electronic circuits and how you can use them to bring your wearable projects from concept to prototype.
Circuits -- Conductive materials -- Switches -- E-textile toolkits -- Making electronics wearable -- Microcontrollers -- Sensors -- Actuators -- Wireless -- Appendix A: Tools -- Appendix B: Batteries -- Appendix C: Resources -- Appendix D: Other neat things -- Appendix E: Microcontroller options.
"Design, prototype, and wear your own interactive garments"--Cover.
Includes index.
Keywords: Wearable technology; Wearable computers -- Design and construction; Human-computer interaction